Morphological integration in developing limbs of Homo sapiens and Papio ursinus - Chiba, Manoj Dayal (My University, 2009)
Previous studies have documented the locomotor pattern of bipedal and quadrupedal primates based on gross morphological or cross-sectional differences. Although these studies provide a measurable amount of understanding they fail to allow one to understand the emergence of these differences ontogenetically. Many researchers have opted to use genetic or epi-genetic factors as reasons for the differences. It has been suggested that the manner in which traits change may be constrained or facilitated by their levels of integration, and therefore morphological integration may be viewed as a source of evolutionary constraint. Ontogenetic samples of 92 humans and 20 baboon skeletons were analyzed for differences and/or similarities using metric and cross-sectional geometric data, of the femur and tibia. The analysis included the computation of regression techniques, bivariate and multivariate analysis. Contrary to expectations, results indicate no significant difference between species. This suggests that ontogenetically both humans and baboons have similar growth trajectories and the epi-genetic factors due to differing locomotory modes have minimal influences. However, both epi-genetic and genetic factors need to be explored further. Furthermore, both metrical and cross-sectional data provide a clear understanding into this pattern of morphological integration and thus should be used together in the analysis of locomotor patterns.